ACCELERATION OF CEMENTITE DECOMPOSITION IN CAST IRON DUE TO PRELIMINARY HOT PLASTIC DEFORMATION - A. I. Pokrovskij; B. B. Hina; I. N. Hrol (Литьë и металлургия)
The experimental investigation of graphitization of preliminary deformed mottled iron is given and the development of valuation system for analysis of graphitization acceleration mechanism is given.